Genetic Variability Studies in Wheat (T. aestivum L.) under Waterlogged Sodic Soils - Verma, P. N.; Singh, B. N.; Vishwakarma, S. R. (International Journal of Bio-resource and Stress Management, 2023)
Genetic diversity analysis helps in selecting genetically diverse parents. Water logging-prone environments are highly diverse and complex and the mechanisms of tolerance to water logging include a large range of traits. This is further evaluated with the aim of prioritizing traits required for waterlogging tolerance of wheat in the field condition. A field experiment was conducted during 2010-11 with 108 bread wheat genotypes to study genetic variability and interrelationship estimates for 11 attributes in wheat under waterlogged sodic soils. The whole experiment was conducted in 2 sets; the first set was irrigated and drained after 24 hr. (control) while second set was grown under waterlogged condition for 10 days after 27 days of sowing. The entries Kharchiya-65 and Perenjori were to be found highest grain yielder under drained and waterlogged condition, respectively. Significant correlation between grain yield and biological yield plant-1, spike weight plant-1, productive tillers plant-1, harvest index, grains spike-1 and 1000-grain weight under both conditions indicated scope for improving grain yield through simultaneous selection. Path analysis further supported and highlighted the importance of biological yield plant-1 and harvest index under drained and waterlogged condition. The cluster analysis grouped the 108 bread wheat genotypes into 11 different clusters under both drained and waterlogged conditions. Hybridization among the genotypes separated by high inter-cluster distance is recommended for getting high heterosis as well as for getting transgressive segregants in F2 generation.